Stylistic Studies in Tere Liye's Novel The Child of the Storm - Juliana mitasari Sumarti; Sudirman Shomary; Noni Andriyani (UIR Press, 2022)
The freedom of use of the language of novel authors resulted in the emergence of different dramatic languages for the author to give rise to aesthetics to his works such as stilistics. The study of stilistics is found in many novels in the form of language disclosure that is able to create an interesting story, so this is always the mainstay of the author in his novel as an attraction. The problem with this study is 1) How is the use of diction (Lexical) in the novel The Storm Child by Tere Liye?, 2) How is the use of dramatic language in the novel The Storm Child by Tere Liye?. This study aims to analyze the use of diction (lexical) and drematic language in the novel The Storm Child by Tere Lliye. In conducting research researchers use descriptive methods with research techniques, namely hermaunetic techniques. The theory that the authors used in this study is Sikana (2005) in the study of stilistics on dramatic language elements and the use of diction. The source of the data in this study is the novel The Storm Child by Tere Liye which is titled 25 subbabs. The results of this study show the use of diction (lexical) in the novel The Storm Child by Tere Liye there are 41 data. In novels many use the selection of words with foreign languages and standard languages. Its dominance in the standard language because the selection of the selected standard word can still describe the content of an interesting story with words or language that is formal in everyday conversation that is still acceptable to the reader and understood. In addition, the dramatic language in the novel The Storm Child by Tere Liye in this study contained 19 data. From the data there are dramatic languages namely metaphors, smiles, personification compounds and sticometry. The dominance of dramatic language in this novel is more about the majas personification of 7 data, this is because the author tries to provide stories with comparisons between objects with objects or humans with objects that seem to have the same character and nature as humans.. So this will be more interesting to readers with the comparisons given in the language and story of the novel. In addition, metaphors as much as 3 data., smile as much as 6 data, and styymetry there are 3 data.